Interval between onset of psoriasis and psoriatic arthritis comparing the UK Clinical Practice Research Datalink with a hospital-based cohort. (25th August 2017) - Tillett, William; Charlton, Rachel; Nightingale, Alison; Snowball, Julia; Green, Amelia; Smith, Catherine; Shaddick, Gavin; McHugh, Neil
Abstract: Objectives: To describe the time interval between the onset of psoriasis and PsA in the UK primary care setting and compare with a large, well-classified secondary care cohort. Methods: Patients with PsA and/or psoriasis were identified in the UK Clinical Practice Research Datalink (CPRD). The secondary care cohort comprised patients from the Bath PsA longitudinal observational cohort study. For incident PsA patients in the CPRD who also had a record of psoriasis, the time interval between PsA diagnosis and first psoriasis record was calculated. Comparisons were made with the time interval between diagnoses in the Bath cohort. Results: There were 5272 eligible PsA patients in the CPRD and 815 in the Bath cohort. In both cohorts, the majority of patients (82.3 and 61.3%, respectively) had psoriasis before their PsA diagnosis or within the same calendar year (10.5 and 23.8%), with only a minority receiving their PsA diagnosis first (7.1 and 14.8%). Excluding those who presented with arthritis before psoriasis, the median time between diagnoses was 8 years [interquartile range (IQR) 2–15] in the CPRD and 7 years (IQR 0–20) in the Bath cohort. In the CPRD, 60.1 and 75.1% received their PsA diagnosis within 10 and 15 years of their psoriasis diagnosis, respectively; this was comparable with 57.2 and 67.7% in the Bath cohort. Conclusion: A similar distribution for the time interval between psoriasis and arthritis was observed in the CPRD and secondary care cohort. These data can inform screening strategies and support the validity of data from each cohort.